The teaming church : ministry in the age of collaboration - Crosby, Robert (Nashville : Abingdon Press, 2012)
A committee is not the same thing as a team. To become a great team, a group must have a goal that is deeply challenging, a leader who is creatively empowering, and a willingness to work within a collaborative community that honors the Bible. The Bible is full of examples of great things accomplished through teaming leaders. Scripture also provides a compelling model from which church communities and teams can learn to live and serve in light of the "Divine Team"--The Trinity. Author Robert C. Crosby provides several innovative ways in which biblical teams reflect the workings and nature of the Trinity and thus the image of God. Revealing what he calls "The Four C's of Great Teams" - The Character, The Carrot, The Coach, and The Context - Crosby shows how successful teams reach their goals more effectively. Conversely, he also addresses the "Four Fatal Teaming Errors" and how to avoid unnecessary, time-consuming missteps. This book provides biblical motivations, vivid examples, and practical approaches for creating a teaming culture in any faith community. Crosby, a leader who has built teams as a senior pastor, youth leader, and university administrator, is now training and mentoring a new generation of pastors and leaders.
The Day Your Group Becomes a Team -- The Team Tour: Great Teams and Teaming Players -- The DNA of a Winning Team -- The Carrot: Teaming Motivation -- Turning Groups into Teams -- Teaming Leadership -- Essential Skills of Teaming Leaders: Unleashing Team Brilliance -- The Divine Team -- Teaming Models and Metaphors: The Images That Help Us Draw Better Circles -- Creating Circles Where People Can Thrive: A Teaming Culture.
Includes bibliographical references.
Keywords: Christian leadership; Church group work; Church group work; Christian leadership